SPECIFIC FEATURES OF THE MANIFESTATION OF BEHAVIORAL TRAITS IN STRESSFUL SITUATIONS IN FUTURE EDUCATORS - Olimova Firuza Aslonovna (Journal of Applied Science and Social Science, 2026)
Abstract. This article examines the specific features of behavioral trait manifestation in stressful situations among future educators. The teaching profession requires a high level of emotional stability, self-regulation, and adaptability, making stress management an essential component of professional preparation. The study analyzes the psychological factors influencing behavior under stress and explores the ways future teachers respond to academic, social, and professional challenges. Particular attention is given to emotional reactions, coping strategies, communication patterns, and adaptive behaviors demonstrated during stressful situations.